2022
DOI: 10.3389/fphy.2021.791736
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Orientation–Dependent Spin Hall Effect in Epitaxial Platinum

Abstract: We report on the spin Hall effect in epitaxial Pt films with well-defined crystalline (200), (220), and (111) orientations and smooth surfaces. The magnitude of the spin Hall effect has been determined by spin–torque ferromagnetic resonance measurements on epitaxial Pt/Py heterostructures. We observed a 54% enhancement of the charge-to-spin conversion efficiency of the epitaxial Pt when currents are applied along the in-plane <002> direction. Temperature-dependent harmonic measurements on epitaxial Pt/Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
(89 reference statements)
0
1
0
1
Order By: Relevance
“…В последнее время особое внимание уделяется исследованию влияния структуры эпитаксиальных пленок металлов на спин-зависимые транспортные свойства. Так, показано, что в некоторых случаях в поликристаллических образцах наблюдается увеличение угла СЭХ по сравнению с таковым для монокристаллических [4].…”
unclassified
“…В последнее время особое внимание уделяется исследованию влияния структуры эпитаксиальных пленок металлов на спин-зависимые транспортные свойства. Так, показано, что в некоторых случаях в поликристаллических образцах наблюдается увеличение угла СЭХ по сравнению с таковым для монокристаллических [4].…”
unclassified
“…Particular attention has been paid in recent studies to the influence of the structure of epitaxial metal films on spindependent transport properties. Specifically, it has been demonstrated that the SHE angle in certain polycrystalline samples increases relative to the corresponding angle in single-crystalline ones [4].…”
mentioning
confidence: 99%